2010
DOI: 10.1007/s11356-009-0281-7
|View full text |Cite
|
Sign up to set email alerts
|

Organocopper complexes during roxarsone degradation in wastewater lagoons

Abstract: Concerns regarding the degradation of roxarsone in wastewater to the more toxic inorganic As may be partially linked to the presence of particulate Cu. The presence of Cu in wastewater-suspended particle surfaces has never been coupled before to organoarsenicals degradation reactions, thus, further studies are needed to elucidate the related reaction mechanisms and pathways. Water depth-dependent solid particle distribution profiles in wastewater storage lagoons could provide empirical evidence towards the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Since arsenate is the most abundant inorganic species resulting from roxarsone degradation this result was expected. (Cortinas et al 2006;Stolz et al 2007;Andra et al 2010). Also, the production of considerable amounts of arsenate and several other roxarsone transformation intermediates was recently confirmed by D' Angelo et al (2012), while litter is accumulated in broiler houses.…”
Section: Consortium Growth and Roxarsone Degradationmentioning
confidence: 74%
“…Since arsenate is the most abundant inorganic species resulting from roxarsone degradation this result was expected. (Cortinas et al 2006;Stolz et al 2007;Andra et al 2010). Also, the production of considerable amounts of arsenate and several other roxarsone transformation intermediates was recently confirmed by D' Angelo et al (2012), while litter is accumulated in broiler houses.…”
Section: Consortium Growth and Roxarsone Degradationmentioning
confidence: 74%
“…Aerobic degradation, although less common than anaerobic processes, has been employed for treatment of roxarsone in swine waste lagoons (Makris et al, 2008a,b). Speciation analysis showed that DMA was the primary degradation product, although nitrophenol and HAPA were also identified (Andra et al, 2010).…”
Section: Microbial Degradation Of Organoarsenicalsmentioning
confidence: 99%
“…Esto ha sido reportado por otros autores tanto para compuestos orgánicos tóxicos como para metales pesados (Campos et al 2009;Campos et al 2011;Silver & Phung 2005). De hecho, los compuestos intermediarios generados durante la biotransformación de ROX son semejantes al ácido 4-hidroxi-3-amino fenil arsénico (HAPA), ácido monometilarsénico (MMA (V)), ácido monometilarsonoso (MMA (III)), ácido dimetilarsínico (DMA (V)), ácido dimetilarsinoso (DMA (III)), óxido de trimetilarsina (TMA (III)) y compuestos inorgánicos como arsenito (As (III)) y en mayor proporción arseniato (As (V)) (Andra et al 2010;Cortinas et al 2006;Stolz et al 2007), pueden producir lisis celular por ser altamente tóxicos para la células. Un ejemplo es el As (V), un análogo de la estructura de fosfato que puede entrar a las células mediante transportadores de fosfato e inhibir la fosforilación oxidativa.…”
Section: Discussionunclassified